2020
DOI: 10.1364/ol.382589
|View full text |Cite
|
Sign up to set email alerts
|

Origin of cell contrast in offset aperture adaptive optics ophthalmoscopy

Abstract: Offset aperture and split detector imaging are variants of adaptive optics scanning ophthalmoscopy recently introduced to improve the image contrast of retinal cells. Unlike conventional confocal scanning ophthalmoscopy, these approaches collect light laterally decentered from the optical axis. A complete explanation of how these methods enhance contrast has not been described. Here, we provide an optical model with supporting in vivo data that shows contrast is generated from spatial variations in refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Our choice of imaging wavelength (796 nm) provided minimal phototoxicity, greater theoretical penetration through the eye’s anterior optics and minimal absorption in the retina without scatter typical of short visible wavelengths. Furthermore, we have previously published a detailed wave-optics simulation to determine the source of contrast in our imaging modality ( Guevara-Torres et al, 2020 ), where we found that the combination of this wavelength and other imaging parameters rendered imaging contrast to translucent cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our choice of imaging wavelength (796 nm) provided minimal phototoxicity, greater theoretical penetration through the eye’s anterior optics and minimal absorption in the retina without scatter typical of short visible wavelengths. Furthermore, we have previously published a detailed wave-optics simulation to determine the source of contrast in our imaging modality ( Guevara-Torres et al, 2020 ), where we found that the combination of this wavelength and other imaging parameters rendered imaging contrast to translucent cells.…”
Section: Discussionmentioning
confidence: 99%
“…By correcting for the eye’s aberrations, single-cell resolution provides detailed imaging of photoreceptors to erythrocytes ( Joseph et al, 2019 ; Liang et al, 1997 ; Roorda and Duncan, 2015 ). Incorporating our recent advance ( Guevara-Torres et al, 2020 ) on AOSLO phase contrast approaches ( Chui et al, 2012 ; Scoles et al, 2014 ; Sulai et al, 2014 ; Guevara-Torres et al, 2015 ; Guevara-Torres et al, 2016 ) allowed deep tissue detection of translucent immune cells. We combined and applied these strategies and serendipitously discovered that immune cells and their dynamics could be imaged without labeling using 796 nm near-infrared light, to which the eye is less sensitive, and at far lower levels (200–500 µW) than multiphoton systems, which can be phototoxic ( Galli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of a combined confocal and nonconfocal AOSLO system is that it allows for confocal imaging of direct backscattered light from waveguiding cones (generally a combination of light scattered at the IS/OS junction and from the cone OS tips 29 , 30 ) and nonconfocal imaging of multiply scattered and refracted light from the IS 28 , 31 at the same location simultaneously. Nonconfocal split-detection allows the scattered light from cone IS to be observed even in cones in which the OSs are nonwaveguiding.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, fluorescent light could also be used to generate a cross-section, which does not produce any signal in OCT. Comparing different modalities, along with their en-face images, may help to elucidate the cellular origin of the observed features on en-face images [44] and/or OIT images.…”
Section: Using Multiply Scattered Light To Generate Retinal Cross-secmentioning
confidence: 99%